Experimental and numerical analysis of side forces in a forging die - Kocańda, Andrzej (Strojniški vestnik, 2008)
Though hot forging dies are subjected mostly to forces acting in the direction of moving tool/slider, some side forces are also developed in the diecavity according to the flow of material in various directions. These forces would be relatively high especially in the cases of non-axisymmetrical or extended forgings what could result in an offset of upper and lower dies causing geometrical inaccuracy of the forging. This paper presents two ways of determining side forces by means of numerical and physical modeling. Two industrial forging processes for the bracket lever and the valve lever were chosen for the analysis. As the result, values and directions of side forces from the beginning up to the end of deformation stage were obtained. Hence some changes in die design or process stages which would minimize the influence of side forces on geometrical inaccuracy of forgings could be introduced. As an example, some ways to minimize the side forces by changing the inclination of parting surface (bracket lever forging) or changing the positioning of perform (valve lever forging) were shown.
Keywords: kovanje; orodja; sile; modeli